The Exposition of Baghdad University ‘s Students to Islamic Sites via Internet - Rashed Abed, Shaima (Opción, 2019)
Electronic sites have great importance and great benefit, and they represent the link between the recipient and many departments and institutions by pro- viding facilities and services. There are several factors that help websites to succeed, including linguistic content, selection of simple title on complexity, and selection of attractive designs, including Islamic sites and their money, of importance and impact in shaping Attitudes, opinions and cultures of the pub- lic. The importance of research is the social dimension that it seeks to achieve by revealing the relationship between the level of exposure to Islamic sites and the implantation and development of Islamic culture in an important, ac- tive and vital group of society. Youth category The researcher used the survey method and the questionnaire tool, which was distributed to students of the University of Baghdad to reach the goals of the research.